The Dynamics of Islamic Legal Epistemology: The Transformation of the Ijtihad Method from the Classical to the Contemporary Era - Eka putra zakran; Maya Surya (ISNU Sumatera Utara, 2026)
This research is based on the dynamics of the development of Islamic legal thought, which shows that the ijtihad method has continuously changed along with the social and intellectual development of Muslims. Since the early days of Islam, law has been understood not only as a textual norm but also as the result of a reasoning process aimed at safeguarding human welfare. Therefore, understanding the history of Islamic legal epistemology is crucial to see how the ijtihad method has evolved from the classical to the contemporary era in response to the challenges of the times. This research aims to analyze the transformation of Islamic legal epistemology and examine the development of the ijtihad method from the classical period, the medieval period, to the modern era. This research uses a qualitative approach with library research methods. Data were obtained from classical books on ushul fiqh, works of Islamic legal thinkers, and contemporary academic literature discussing the epistemology of Islamic law. The analysis is conducted using historical and conceptual approaches to trace the development of ijtihad methodology and the paradigm shift in Islamic legal thought. The results show that during the classical period, the foundations of Islamic legal epistemology were formed through the systematization of ushul fiqh formulated by scholars, particularly Imam al-Syafi'i. During the medieval period, the development of legal thought experienced a phase of school of thought consolidation, marked by the strengthening of the practice of taqlid (religious taqlid) and the emergence of debates regarding the closure of the door to ijtihad. Meanwhile, in the modern era, various attempts to reconstruct the ijtihad method emerged through the maqasid al-shariah approach, legal contextualization, and the thoughts of figures such as Fazlur Rahman and Yusuf al-Qaradawi. This research concludes that Islamic legal epistemology is dynamic and adaptive to changing times. Therefore, the development of contemporary Islamic law needs to integrate a textual approach, maqasid al-shariah, and an understanding of social reality to ensure ijtihad remains relevant in addressing the issues of modern society.